Analisis of an investigative teaching sequence proposal for the UV radiation (Research, Society and Development, 2022)
In this work we aim to analyze the potential of a proposal for an Investigative Teaching Sequence (ITS) on Radiation and Radioactivity theme. In this purpose, the investigation involved carrying out an experiment using black light and sunscreen with different Sun Protection Factors (SPF). This activity was developed with 36 students from two class groups of the 2nd year of High School (EM) from a public school in Campo Mourão city/PR - Brazil. As a data record instrument, we used the justifications given by the participants to the question which finalizes the ITS. To analyze of these responses we use the framework of Textual Discursive Analysis (TDA). The activity made the scientific argumentation and the interaction possible between the students and the graduates, arousing the taste for Science. The results presented suitable justifications regarding the use of sunscreen, highlighting the importance of its use to prevent skin diseases and the learning of physics concepts related to radiation.